Public Budget and the Roles of Legislative and Executive Power Regarding It with Reference to Iraq)2004-2011) - سالم, سالم عبد الحسين (Journal of Economics and Administrative Sciences, 2012)
The public budget is regarded a main tool for economic and social development. The preparation of the public budget constitute an important stream which enriches the developmental efforts and the definition of its priorities, therefore it is the focus point of many specializations. The public budget has numerous functions. It is a means to precise and to execute the political and economic goals of the executive authority, a mirror of the economic structure which reflects its strength and weakness points, specifies its revenues and others. Since the parliament is the voice of the society which expresses its interests, then, it must monitor the performance of the government so that the participation of the legislative authority in the preparation of the public budget and the final account has become a traditional part of its responsibilities, therefore it encouraged the appearance of a new trend which classifies the public budget as a fourth function of the parliament in addition to its legislative, monitory and representative functions. The public budget is often prepared by the executive authority for many reasons and justifications. Through the study of the experiments of many countries on the subject, it became clear that they differ regarding the roles, effect tools and interference. It became clear; too, that some parliaments have committees specialized in the study of public budget. If we compare those experiments to the state in Iraq, we find that there is no defect within the Iraqi legal frame which specifies the role of the legislative authority in the public budget and the final account. The problem lies in the fact that the Iraqi parliament does not adopt an effective role regarding both of them. Many articles of the Iraqi 2005 Constitution, Law for Financial Management 2004 and some of the articles of the Internal Bylaw of the Iraqi parliament specify the general and timing frames for the preparation of the public budget and the final account until their approval. It is worth mentioning that the final account in Iraq did not meet the attention it worth, especially from the Iraqi parliament. Its presentation by the executive authority is usually delayed from the dead points named by laws. The investment expenditures have gained, as average, 19% of the public expenditures throughout 2006- 10, while the percentages of the achievement of the investment projects have amounted to 61%. It seems that the general rule adopted in the preparation of the public budget in Iraq throughout 2006- 10 has been a preparation of a public budget with a planned deficit turns to actual surplus.